Competence Acquisition Issues and Challenges: The Experiences of Accountancy Trainees - Selamat, R.; Idris, N. (Journal of Advanced Research in Business and Management Studies, 2020)
This paper discusses the findings of two Exploratory Focus Group Discussions (FGDs) held with accountancy trainees who are pursuing to become professional accountants. The FGDs are part of a bigger research which aims to inform an understanding of how accountancy trainees acquire competence at the workplace. Two separate FGDs were conducted with selected trainees who are in a process of qualifying for the Chartered Institute of Management Accountant (CIMA) and Association of Chartered Certified Accountants (ACCA). The findings of both FGDs pointed to trainees’ related issues such as varying working and learning experiences, juggling between work and study commitment, tuition provider and teaching styles, and comparison of trainees’ performances. Other issues are organizational related issues such as the welfare and benefits of trainees, contract and confirmation, and the management of the training program. A striking outcome of comparison of the transcription was that the findings showed some clear similarities but also some differences in the accounts given by the separate group of trainees. This study also discusses the implications of the findings on the role of HR and line managers to facilitate trainees’ competence acquisition via workplace learning.